2022
DOI: 10.1001/jamanetworkopen.2021.46519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinical Decision Support at Community Health Centers on the Risk of Cardiovascular Disease

Abstract: IMPORTANCE Management of cardiovascular disease (CVD) risk in socioeconomically vulnerablepatients is suboptimal; better risk factor control could improve CVD outcomes. OBJECTIVE To evaluate the impact of a clinical decision support system (CDSS) targeting CVD risk in community health centers (CHCs). DESIGN, SETTING, AND PARTICIPANTSThis cluster randomized clinical trial included 70 CHC clinics randomized to an intervention group (42 clinics; 8 organizations) or a control group that received no intervention (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In that study, the CDS was not part of a sociotechnical system and was not integrated with provider workflows [51]. The low use rate of an EHR-based CDS for cardiovascular risk reduction in community health centers was also reported in a cluster randomized clinical trial that focused on CDS technology [52,53].…”
Section: Principal Findingsmentioning
confidence: 97%
“…In that study, the CDS was not part of a sociotechnical system and was not integrated with provider workflows [51]. The low use rate of an EHR-based CDS for cardiovascular risk reduction in community health centers was also reported in a cluster randomized clinical trial that focused on CDS technology [52,53].…”
Section: Principal Findingsmentioning
confidence: 97%
“…Obviously, the observed CDSS effects on guideline adherence need to be confirmed by additional high quality, preferably two-armed, or randomized trials, but it should be acknowledged that the conduction of such trials is complex and challenging. However, early evidence from a randomized study on a noncancer indication suggested a clear benefit from CDSS usage [66].…”
Section: Evidence: Clinical Decision-support System Usage Increases G...mentioning
confidence: 99%
“…In JAMA Network Open , Gold et al share results from their cluster randomized clinical trial assessing the impact of CV Wizard, an electronic health record (EHR)–embedded clinical decision support system (CDSS), on cardiovascular risk reduction in patients served by community health centers (CHCs). By implementing a previously validated CDSS in underresourced health care facilities that predominantly serve socioeconomically vulnerable patients, the authors generated 2 particularly important findings.…”
mentioning
confidence: 99%
“…Gold et al implemented CV Wizard in multiple CHC organizations as an intervention to change clinician and patient behavior important for reducing patients’ ASCVD risk. In doing so, they had all the components of the practical, robust implementation and sustainability model (PRISM), a well-established implementation science framework, of Feldstein and Glasgow .…”
mentioning
confidence: 99%
See 1 more Smart Citation